Retrospective Diagnosis of a Novel ACAN Pathogenic Variant in a Family With Short Stature: A Case Report and Review of the Literature - Mancioppi, Valentina; Prodam, Flavia; Mellone, Simona; Ricotti, Roberta; Giglione, Enza; Grasso, Nicolino; Vurchio, Denise; Petri, Antonella; Rabbone, Ivana; Giordano, Mara; Bellone, Simonetta (Frontiers in Genetics, 2021)
Short stature is a frequent disorder in the pediatric population and can be caused by multiple factors. In the last few years, the introduction of Next Generation Sequencing (NGS) in the molecular diagnostic workflow led to the discovery of mutations in novel genes causing short stature including heterozygous mutations in ACAN gene. It encodes for aggrecan, a primary proteoglycan component specific for the structure of the cartilage growth plate, articular and intervertebral disc. We report a novel ACAN heterozygous pathogenic variant in a family with idiopathic short stature, early-onset osteoarthritis and osteoarthritis dissecans (SSOAOD). We also performed a literature review summarizing the clinical characteristic of ACAN’s patients. The probands are two Caucasian sisters with a family history of short stature and osteoarthritis dissecans. They showed dysmorphic features such as mild midface hypoplasia, brachydactyly and broad thumbs, especially the great toes. The same phenotype was presented in the mother who had had short stature and suffered from intervertebral disc disease. DNA sequencing identified a heterozygous pathogenic variation (c.4390delG p.Val1464Ter) in the sisters, with a maternal inheritance. The nonsense mutation, located on exon 12, results in premature truncation and presumed loss of protein function. In terms of treatment, our patients underwent recombinant human growth hormone replacement therapy, associated with gonadotropin releasing hormone therapy, in order to block early growth cessation and therefore reach a better final height. Our case suggests that SSOAOD ACAN related should be considered in the differential diagnosis of children with autosomal dominant short stature and family history of joints disease.